Analyzing sharing experiences in government sector based on shared service perspectives - Hafizi, R. (Asian Research Publishing Network, 2016)
Shared service exists both in private and in public sectors. The promising benefits of shared service make many governments try to implement it in different ways. This paper describes the experiences of using shared service in government sector from i) process, ii) technical, and iii) strategic perspectives. It is done by describing sharing as well as technology and organizational performance of those shared service perspectives in the government sectors. The relevant information was gathered by using conventional content analysis from three selected online databases. Overall, shared services in government have demonstrated significant effort toward successful implementation. Those shared services have aim to reduce cost and increase the effectiveness of services for many public users and business partners. It is done whether by focusing on implementation approach, technology, or step by step of implementation process. The researchers also found that there are some differences in treating shared service from different perspectives. Future research shall do identification the differences of success factors from those shared service perspectives. Future research also might identify the risks and values for each of those shared service perspectives.